(untitled) (Global Journal of Advanced Engineering Technologies and Sciences, 2018)
To analyze the effect of the addition of biodiesel on the oxidative stability of its blends with diesel up to 20% of biodiesel, ASTM 6186 method was used at 290psi with pure oxygen and air using pressurized differential scanning calorimetry (PDSC), to see at different oxygen concentrations, the influence of the biodiesel content at high pressure levels on the auto-ignition temperature. As the PDSC heating chamber temperature increases, the thermal instability onset temperature (Tauto-ignition) of the sample corresponds to its auto-ignition temperature followed by combustion, which is the basis of diesel engine operation at high pressures. PDSC analyses with pure oxygen were also carried out at 100 psi pressure, to see if at this lower initial pressure and oxygen concentration there would be different biodiesel content influence on the thermal oxidative stability. At these elevated pressures, it was verified that the pure diesel oil present the highest ignition temperature and in the blend samples, the higher is the biodiesel content, the lower is the thermo-oxidative stability temperature of the blend, decreasing respective ignition delay. The PDSC combustion peaks at 290 psi in air were wider than those in pure oxygen, indicating lower combustion rates due to the lower concentration of oxygen at same operating pressure. However, the thermo-oxidative stability temperatures as a function of the biodiesel content were very close in both cases. In pure oxygen, as the pressure increases from 100 to 290psi, the thermo-oxidative stability of the diesel/biodiesel blends increases due to the decreased volatility of the diesel component.The correlation that shows how the increase of biodiesel content decreases Tauto-ignition, changes from a linear to a polynomial function of 2nd order degree. Additionally, as more biodiesel is added to the diesel oil, the increase of the operating pressure increases the formation of carbonaceous residues, which explains the increased problems of residue formation in diesel cycle engines when using diesel / biodiesel blends